THE ANALYSIS OF SPATIAL POTENTIAL OF AGRICULTURAL COMPLEX OF THE REPUBLIC OF BURYATIA AS A SINGLE SOCIO-ECONOMIC MECHANISM - Ekaterina V. Galdanova (Статистика и экономика, 2016)
The article analyzes the spatial development of agriculture in the region and identified the prospects of the industry in the modern world.